Strategi Kendali Daya Baterai-Superkapasitor Berbasis Variable Time Constant dengan Pendekatan Gradien - Ariq Kusuma Wardana; Imron Ridzki; Arinalhaq Fatachul Aziiz; Ricto Yudi Wicaksono (Elposys: Jurnal Sistem Kelistrikan, 2026)
Photovoltaic (PV) power generation is inherently intermittent, causing power fluctuations that can degrade DC-bus voltage stability and overall system performance. To address this issue, this study proposes an adaptive variable time constant (VTC) control strategy with a gradient-based approach for battery–supercapacitor power management in a stand-alone PV system. In the proposed method, the low-pass filter (LPF) frequency is adjusted adaptively according to the gradient of the total compensation current. A higher gradient increases the LPF frequency to improve transient response, while a lower gradient helps maintain stable operation and supports balanced power sharing between the battery and supercapacitor. The proposed strategy was evaluated in MATLAB/Simulink under two irradiation-change scenarios, namely undershoot (1000 to 750 W/m²) and overshoot (750 to 1000 W/m²), and compared with fixed time constant (FTC) methods. The results show that the proposed VTC strategy yields the lowest average DC-bus voltage deviation of 9.50%, compared with 9.66% for FTC minimum and 9.68% for FTC maximum. In addition, it maintains a low average supercapacitor state-of-charge deviation of 0.0150%, equal to FTC maximum and significantly lower than FTC minimum (0.1628%). These findings indicate that the proposed adaptive VTC strategy improves voltage regulation while maintaining effective battery-supercapacitor power sharing under dynamic PV operating conditions.